2019
DOI: 10.1523/jneurosci.0163-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory Action of Picomolar Extracellular Aβ42 Oligomers on Presynaptic and Postsynaptic Mechanisms Underlying Synaptic Function and Memory

Abstract: Failure of anti-amyloid-␤ peptide (A␤) therapies against Alzheimer's disease (AD), a neurodegenerative disorder characterized by high amounts of the peptide in the brain, raised the question of the physiological role of A␤ released at low concentrations in the healthy brain. To address this question, we studied the presynaptic and postsynaptic mechanisms underlying the neuromodulatory action of picomolar amounts of oligomeric A␤ 42 (oA␤ 42) on synaptic glutamatergic function in male and female mice. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 89 publications
8
69
0
Order By: Relevance
“…One of the problems in relating these papers to the results presented here is that it is hard to equate superfusion of synthetic peptides to endogenous production of Aβ from mutated APP. Nevertheless, the published data using exogenous application of Aβ peptides are consistent with what we have shown, because diverse changes in synaptic activity have been documented, both increases and decreases (Gulisano et al, 2019; Kelly et al, 1996; Parameshwaran et al, 2007; Ripoli et al, 2014; Yao et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…One of the problems in relating these papers to the results presented here is that it is hard to equate superfusion of synthetic peptides to endogenous production of Aβ from mutated APP. Nevertheless, the published data using exogenous application of Aβ peptides are consistent with what we have shown, because diverse changes in synaptic activity have been documented, both increases and decreases (Gulisano et al, 2019; Kelly et al, 1996; Parameshwaran et al, 2007; Ripoli et al, 2014; Yao et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…4). Whilst low levels of Aβ can increase dendritic spine density [194], increase the number of docked vesicles [92], enhance glutamate release, promote excitotoxicity, and disrupt calcium homeostasis (particularly in early stages of disease) [7,35,225], Aβ production after synaptic activity could also act via negative feedback to prevent hyperactivity [123]. Indeed, Aβ can induce spine collapse and synapse loss [231,274], increase the proportion of silent neurons [35], and disrupt neurotransmitter release via depletion of presynaptic PIP 2 [99] .…”
Section: Regulating Neuronal Hyperexcitability: Could Tau and Aβ Actmentioning
confidence: 99%
“…The Slutsky lab elegantly demonstrated that increasing Aβ by neprilysin inhibition increases SV recycling, while decreasing physiological Aβ levels by anti-Aβ antibody-promoted degradation, in contrast, decreases SV recycling (Abramov et al, 2009). More recent data indicate that exogenous picomolar preparations of oligomeric Aβ42 can augment neurotransmitter release and the length of the postsynaptic density, resulting in a late-LTP (Gulisano et al, 2019). The mechanisms of how endogenous Aβ regulates synaptic vesicle recycling and PSD recruitment for modulating synaptic transmission and plasticity are unclear.…”
Section: Aβ Physiological Role At Synapsesmentioning
confidence: 99%
“…The mechanisms of how endogenous Aβ regulates synaptic vesicle recycling and PSD recruitment for modulating synaptic transmission and plasticity are unclear. Some evidence indicates that Aβ can bind to alpha7nicotinic acetylcholine receptors (Puzzo et al, 2008;Gulisano et al, 2019) to induce presynaptic calcium entry. Overall, the evidence points to an Aβ physiological role, but it is still not clear which form of Aβ is relevant.…”
Section: Aβ Physiological Role At Synapsesmentioning
confidence: 99%